2018
DOI: 10.3389/fnmol.2017.00450
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lateralization in Mice Is Associated with Zinc Signaling and Altered in Prenatal Zinc Deficient Mice That Display Features of Autism Spectrum Disorder

Abstract: A number of studies have reported changes in the hemispheric dominance in autism spectrum disorder (ASD) patients on functional, biochemical, and morphological level. Since asymmetry of the brain is also found in many vertebrates, we analyzed whether prenatal zinc deficient (PZD) mice, a mouse model with ASD like behavior, show alterations regarding brain lateralization on molecular and behavioral level. Our results show that hemisphere-specific expression of marker genes is abolished in PZD mice on mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
(111 reference statements)
1
28
2
Order By: Relevance
“…Peça et al (2011) reported an enlarged striatum earlier in the same model. An increased striatal volume in the PZD model was already reported by us earlier with a different analysis method (Grabrucker et al, 2018). It can be concluded that basal ganglia enlargement is a common phenomenon in PZD mice and SHANK3 deficiency, however, it might be dosage-dependent of the remaining isoforms.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Peça et al (2011) reported an enlarged striatum earlier in the same model. An increased striatal volume in the PZD model was already reported by us earlier with a different analysis method (Grabrucker et al, 2018). It can be concluded that basal ganglia enlargement is a common phenomenon in PZD mice and SHANK3 deficiency, however, it might be dosage-dependent of the remaining isoforms.…”
Section: Discussionsupporting
confidence: 73%
“…The PZD model has been shown to display a reduction of excitatory synapses in this area (Grabrucker et al, 2014), where zinc was also shown to interact with SHANK3 at the postsynaptic density. Further, an altered brain lateralization, which among others, affects the dopaminergic transmission in the striatum of these mice was reported (Grabrucker et al, 2018). On behavioral level, this correlates with stereotyped repetitive behaviors such as abnormal circling and altered marble burying that has been reported in PZD mice (Grabrucker et al, 2016), but also other ASD mouse models.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our finding in WT mice that shows mostly bilateral CAPs is in line with this observation. On the other hand, in mouse models of autism spectrum disorder, brain lateralization, especially in the striatum, has been reported using MRI and immunohistochemistry (Grabrucker et al 2018). Therefore, right-lateralization of prominent CAPs in TG mice is an interesting finding that needs to be further investigated.…”
Section: Resting-state Markers Of Alzheimer's Diseasementioning
confidence: 98%
“…Two animal models of ASD involved abnormalities in Zn metabolism and demonstrate abnormalities in brain development. The prenatal Zn-deficient mouse model of ASD demonstrates enlargement of the thalamus 43 and striatum 44 , and an absence of lateralization of dopamine receptor 1 in the striatum 44 . Male Zn transporter 3 null mice demonstrate ASD-type behaviors and increased cortical volume and neurite density 45 .…”
Section: The Importance Of Copper and Zinc Metabolismmentioning
confidence: 99%